HUBUNGAN KEPATUHAN DIET DENGAN KUALITAS HIDUP PADA PASIEN PENDERITA DIABETES MELLITUS TIPE 2 DI RSUD Dr. PIRNGADI KOTA MEDAN - Purba, Sri Dearmaita; Sijabat, Flora; Siregar, Rinco (JURNAL KEPERAWATAN, 2023)
Background: Diabetes Mellitus (DM) is a priority public health problem in both developed and developing countries because the incidence of the disease continues to increase every year. The quality of life of people with Diabetes Mellitus is influenced by several factors, one of which is dietary adherence. Objectives: to determine the relationship between dietary adherence and quality of life in patients with type 2 Diabetes Mellitus at RSUD Dr. Pirngadi, Medan city. Methods: The type of research used in this research is quantitative with a cross-sectional research design. The total population in this study was 385 people and the sample selection method used accidental sampling and obtained a total sample of 80 people. Results: Dietary adherence in patients with Diabetes Mellitus was included in the obedient category, namely 67.5% and quality of life in patients with Diabetes Mellitus, was classified as equally good and bad, namely 50%. The results of data analysis with the Chi-Square test were obtained with a significance level of <0.05, the result was p = 0.000. Conclusion: There is a significant relationship between dietary adherence and quality of life in Type 2 Diabetes Mellitus patients at RSUD Dr. Pirngadi, Medan City, so it is hoped that he will always adhere to the diet. Keywords: Diabetes Mellitus; Dietary Compliance; Quality of Life.